Pendugaan Parameter Genetik dan Seleksi Galur Mutan Sorgum (Sorghum bicolor (L.) Moench) di Tanah Masam (Estimation of Genetic Parameters and Selection of Sorghum Mutant Lines under Acid Soil Stress Conditions) - Sungkono Sungkono; Trikoesoemaningtyas Trikoesoemaningtyas; Desta Wirnas; Didy Sopandie; Soeranto Human; Muhammad Arif Yudiarto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Sorghum is one of high value commodities for food and energy security due to its wide adaptation. The objectives of this research were to study some genetic parameters of sorghum agronomic traits grown under acid soil conditions and to select aluminum-tolerant sorghum mutant lines.  The selection was conducted in an augmented design with 61 lines at the field research station of B2TP-BPPT Lampung. Genetic materials used were mutant lines developed throught gamma irradiation.  The results showed that there was significant differences among the mutant lines for  some agronomic characters observed.  The heritability estimates for agronomic characters were classified as intermediate to high.  Selection based on seed weight and biomass production resulted three best sorghum mutan lines i.e ZH30-29-07, ZH30-30-07, and ZH30-35-07.  These lines showed the best yield and biomass production under acid soil condition.   Key words:  sorghum, acid soil, heritability, selection